2021
DOI: 10.1155/2021/5436793
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based CT Imaging in Diagnosing Myeloma and Its Prognosis Evaluation

Abstract: Imaging examination plays an important role in the early diagnosis of myeloma. The study focused on the segmentation effects of deep learning-based models on CT images for myeloma, and the influence of different chemotherapy treatments on the prognosis of patients. Specifically, 186 patients with suspected myeloma were the research subjects. The U-Net model was adjusted to segment the CT images, and then, the Faster region convolutional neural network (RCNN) model was used to label the lesions. Patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These alternative algorithms achieved DSCs or AUCs above 0.7, which is on par with the median performance of the U-Net models. However, U-Net variations have been tried in a greater number of studies and demonstrated performance as high as 0.9821 in this cohort ( 58 ), indicating that U-Net may be more suitable at present day for achieving maximal performance.…”
Section: Discussionmentioning
confidence: 83%
“…These alternative algorithms achieved DSCs or AUCs above 0.7, which is on par with the median performance of the U-Net models. However, U-Net variations have been tried in a greater number of studies and demonstrated performance as high as 0.9821 in this cohort ( 58 ), indicating that U-Net may be more suitable at present day for achieving maximal performance.…”
Section: Discussionmentioning
confidence: 83%
“…Of the 33 studies that applied ML techniques to diagnose a hematological malignancy or to differentiate it from another disease state or malignancy ( Table 1 ), 18 were designed to establish and train ML models to discriminate gliomas [predominantly GBM from PCNSL ( 29 31 , 34 37 , 40 42 , 44 , 45 , 49 , 50 , 53 56 )] using features extracted from FDG-PET [one study ( 29 ),] or MRI ( 30 , 31 , 34 37 , 40 42 , 44 , 45 , 49 , 50 , 53 56 ) images. The remaining studies belonged to two major categories: those developing models to discriminate solid hematological malignancies from other benign and malignant lesions at other sites [nasopharyngeal carcinomas from nasopharyngeal lymphoma ( 46 , 48 ), idiopathic orbital inflammation from ocular adnexal lymphoma ( 33 ), thymic neoplasm from thymic lymphoma ( 14 ), breast carcinoma from breast lymphoma ( 15 ), lymphoma from normal nodes ( 43 ), or multiple myeloma from bone metastases ( 51 )] and those that detect the location of hematological malignancies either at diagnosis or during the disease course [location of ( 18 ) or evolving/residual lymphoma ( 32 ) or leukemia ( 17 ) or bone marrow involvement with multiple myeloma ( 16 , 38 , 47 , 52 ) or mantle cell lymphoma ( 39 )].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to improve the quality of CT images. In recent years, the use of artificial intelligence algorithms for processing medical images is a major trend in medical imaging [ 20 ]. Threshold segmentation on the basis of intelligent algorithms is the most common method for image segmentation.…”
Section: Discussionmentioning
confidence: 99%